"HansaWorld" programmatūras izstrāde un ieviešana - Žunna-Veličko, Katrīne (Latvijas Universitāte, 2012)
Diplomdarba problēmas būtība ir programmatūras ieviešanas efektivitātes paaugstināšana. Efektivitātes paaugstināšana nevar būt mūžīga, ja, ieviešot programmatūru, gadu no gadiem izmanto vienu metodi, neveicot tās uzlabojumus. Diplomdarba mērķis ir veikt HansaWorld programmatūras izstrādes un ieviešanas metodes salīdzinošo analīzi ar citām izstrādes un ieviešanas metodēm un izstrādāt rekomendācijas HansaWorld programmatūras izstrādes un ieviešanas metodes uzlabošanai. Mērķu sasniegšanai autors darbā veica sekojošus uzdevumus – pētīja HansaWorld programmatūras izstrādes un ieviešanas metodi, salīdzināja to ar citām programmatūras izstrādes un ieviešanas metodēm, kā arī analizēja HansaWorld programmatūras izstrādes un ieviešanas metodi esošos projektos un piedāvāja tās uzlabojumus. Ņemot vērā izvirzītos uzdevumus, darba struktūra ir izveidota sekojoša: Pirmajā nodaļā autors iepazīstas ar uzņēmuma misiju un struktūru, analizē pamatdarbības procesus un ekonomiskos rādītājus. Otrajā nodaļā autors veic uzņēmuma piedāvāto produktu un pakalpojumu analīzi. Trešajā nodaļā autors veic uzņēmumā izmantotās programmatūras izstrādes un ieviešanas metodes salīdzinājumu ar Klasiskās ūdenskrituma un Spējās izstrādes metodēm. Ceturtajā nodaļā autors analizē savu līdzšinējo pieredzi par HansaWorld programmatūras izstrādi un ieviešanu uzņēmumos. Darbā uzstādīto mērķu sasniegšanai tika izmantota analītiskā pētījuma metode. Darbā veiktā analīze un pētījums pamatojas uz zinātnisko literatūru, internetā publicētiem materiāliem, uzņēmuma materiāliem un autora personīgo pieredzi.

The essence of the problem researched in the entire work is the increase in effectiveness of software establishment. The increase in effectiveness will not be perpetual if having established a software one uses the same method without making any improvements in the course of time. The aim of the entire work is to do a comparative analysis of development and establishment methods of HansaWorld software as compared to other development and establishment methods as well as to formulate recommendations for the enhancement of HansaWorld software development and establishment methods. To achieve the before-mentioned aim the following objectives have been pursued by the author of the entire work – to research HansaWorld software development and establishment method, to compare the method with the other software development and establishment methods as well as to analyse HansaWorld software development and establishment methods in existent projects and to offer enhancements to the methods. Taking into consideration the research objectives the organization of the entire work is the following: In the first part of the work the author gets acquainted with the enterprise’s mission and its organizational chart, analyses the main business processes and economical indices. In the second part of the work the author analyses products and services offered by the enterprise. In the third part of the work the author compares the software development and establishment methods performed by the enterprise with Classical Waterfall and Agile methods. In the fourth part of the work the author analyses her previous experience with HansaWorld software development and establishment in enterprises. As a result the author offers to improve two of the five processes of HansaWorld development and establishment method that would allow to economize on enterprise’s time and financial resources. The author offers to supplement and to increase the effectiveness of HansaWorld development and establishment method that would make the presentation of software more successful and it would allow to identify and duly eliminate the problems arising in the course of software establishment and development. To achieve the before-mentioned objectives an analytical research method has been used. The analysis and the research performed within the framework of the entire work is based on scientific literature, Internet resources and personal experience of the author of the work.
"HansaWorld" software implementation
Keywords: Vadībzinātne